Rice Husk Ash: A Promising Heavy Metal Adsorbent For Wastewater Treatment - Kumalasari, Meiyanti Ratna; Beladona, Siti Unvaresi Misonia; Gracia, Amanda Natania; Sugiyani, Tina; Wulandari, Oktavia Rahmi; Imelya, Marsya; Syaima, Husna; Hanif, Qonita Awliya (Walisongo Journal of Chemistry, 2024)
The primary polluter of the environment is liquid waste. Silica is one substance that can be utilized to minimize water pollution. Silica can be produced from agricultural biomass waste, such as rice husk ash. This study investigated the preparation of rice husk ash and the optimal synthesis method for producing bio-silica. A literature review of studies on rice husk ash, heavy metals, and adsorbents was conducted. The findings indicated that boiling rice husk at 800°C and washing with HCl produced high-purity silica. XRD (X-ray diffraction), FT-IR (Fourier transform infrared) spectrophotometers, and ED-XRF (Energy Dispersive X-ray fluorescence) were employed to characterize the rice husk ash. The precipitation, sol-gel, acidification, and hydrothermal methods were compared for bio-silica synthesis. The synthesized bio-silica can be used as a heavy metal absorbent for various metal ions, including Pb2+, Zn2+, Mn2+, Cu2+, As3+, As5+, and Cd2+.